P069 What impact has tendering had on trainees? The Results of a National Survey of Trainees and Newly Appointed Consultants by BASHH Trainees Collaborative for Audit, Research and Quality Improvement Projects. (30th June 2016) - Wiggins, Helen; Hartley, Anna; Ahmed, Nadia; Clarke, Emily; Foley, Elizabeth; Carlin, Elizabeth; Waters, Laura
Abstract : Background/introduction: In April 2013, local authorities gained responsibility for commissioning services for sexual health in England. With many services going to tender and resultant change in services or service provider, there is anecdotal evidence that this has impacted on the education, training and morale of genitourinary medicine (GUM) trainees. Aim(s)/objectives: To evaluate the impact of tendering on GUM trainees. Methods: An electronic survey designed by the British Association for Sexual Health and HIV Trainees' Collaborative for Audit, Research and Quality Improvement Projects (T-CARQ) was distributed to GUM trainees and newly appointed consultants. Results: 82 individuals responded, (74% GUM trainees, 25% newly appointed consultants, 1% Locum appointed for Service). 63% (45/72) had experience of training within a service which was being tendered. Of these, 59% (24/41) felt their training was not considered and 20% (8/41) felt that it was. 44% (18/41) felt adequately supported. 30% (12/40) reported active participation in the tendering process. On a scale of 0 (no impact) to 5 (major impact), the median score for impact of tendering on training was 2. The positive/negative impact of tendering on different training elements was rated; other than management experience the overall impact on all parameters was negative namely morale, senior support and education. Discussion/conclusion: This survey describes the variable impact of service tendering on GUM training. Our recommendations for maintaining training standards despite tendering include: actively involving trainees and education partners, inclusion of specialist GUM training in service specifications, development of guidance for commissioners and services for the management of GUM training within tendering.